Effectiveness and Safety of Yi Shen Juan Bi Pill for Rheumatoid Arthritis: A Systematic Review and Meta-analysis - Gyoungeun Park; Ga-young Kim; You Jeong Han; Min-Seop Hwang; Seung-Deok Lee; Kyung-Ho Kim; Jong-Hwa Yoon; Eun-Jung Kim; Won-Suk Sung (Journal of Acupuncture Research, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation affecting multiple joints and organs. Interest in traditional Chinese medicine (TCM) treatment is increasing owing to its effectiveness in disease control and relieving symptoms. The Yi Shen Juan Bi Pill (YSJB) is an antirheumatic TCM formula. Therefore, this systematic review (SR) and meta-analysis aimed to assess the therapeutic effect and safety of YSJB. Randomized controlled trials (RCTs) were searched from worldwide databases. Primary outcomes were disease activity scores. Secondary outcomes included laboratory results and adverse events (AEs). After screening the identified studies, 14 involving 1,497 participants were finally included. One study investigated YSJB as monotherapy, whereas 13 explored its use in combination with conventional medication. Statistically, YSJB showed significant results for the effective rate and a part of joint scale and laboratory results regardless of treatment type (monotherapy or combination therapy) and no significant difference in AEs was observed between two groups. The findings from this SR indicate the therapeutic potential of YSJB in treating RA. However, high heterogeneity, risk of bias, and the small number of RCTs hinder drawing definitive conclusions about its efficacy and clinical application. Therefore, further high-quality studies are required.